Spatial-temporal variability of soils' acidity of Northern taiga forests at lower technogenic load - Sukhareva T. A. (Vestnik MGTU, 2018)
The condition of soil under the influence of airpollutions сopper-nickel smelter "Severonickel" (Monchegorsk, the Murmansk region) have been analyzed. The spatial-temporal dynamics of acidity of Al-Fe podzolic organic soil horizon in the process of technogenic digression of spruce and pine forests has been performed. The studies conducted in 1992 and 2007 on fixed sample plots at different distances from the emission source. Parcellary differences have been found in background spruce forest, where the actual acidity of organic soil horizon spruce parcels is lower than between crown space. Under air pollution parcellary differences of soil acidity are not expressed. In the pine forests the spatial dynamics is characterized by reduced actual and hydrolytic acidity of the organic horizon and the growing exchange of aluminium along a gradient of atmospheric pollution. In defoliating spruce forests and sparse forests the actual soil acidity reduction is observed only in between crown spaces, and hydrolytic soil acidity – in both parcels. The stage of initial defoliation of the crowns of coniferous trees, most remote from the source of emission of pollutants is identified. At this stage, the organogenic horizon of the spruce soils is more acidic than in the undisturbed phytocenosis, and the hydrolytic acidity of the soils remains at the background level. Under the reduction of atmospheric emissions soil acidity decreased in defoliating forests in 2007. In the immediate vicinity of the smelter (7–10 km) soil pH has not changed during the study period. In the pine defoliating forests and sparse forests hydrolytic soil acidity has increased. In spruce forests under atmospheric pollution, the level of hydrolytic and exchange acidity has decreased, with the exception of the stages of initial defoliation of North taiga forests. The exchange soil acidity, the content of the exchange of aluminium and exchange of hydrogen reliably increase at this stage of forest digression. The results of the research can be used in monitoring environment, assessing soil fertility of forest ecosystems under the influence of natural and technogenic factors and contribute to the development of methods of disturbed soils' rehabilitation.